A Proinflammatory Cytokine Network Profile in Th1/Type 1 Effector B Cells Delineates a Common Group of Patients in Four Systemic Autoimmune Diseases. Issue 8 (9th July 2021) - Simon, Quentin; Grasseau, Alexis; Boudigou, Marina; Le Pottier, Laëtitia; Bettachioli, Eléonore; Cornec, Divi; Rouvière, Bénédicte; Jamin, Christophe; Le Lann, Lucas; ,; ,; Borghi, Maria Orietta; et al.
Abstract : Objective: The effector T cell and B cell cytokine networks have been implicated in the pathogenesis of systemic autoimmune diseases, but the association of these cytokine networks with the heterogeneity of clinical manifestations and immune profiles has not been carefully examined. This study was undertaken to examine whether cytokine profiles can delineate distinct groups of patients in 4 systemic autoimmune diseases (systemic lupus erythematosus, Sjögren's syndrome, rheumatoid arthritis, and systemic sclerosis). Methods: A total of 179 patients and 48 healthy volunteers were enrolled in the multicenter cross‐sectional PRECISE Systemic Autoimmune Diseases (PRECISESADS) study. Multi‐low‐dimensional omics data (cytokines, autoantibodies, circulating immune cells) were examined. Coculture experiments were performed to test the impact of the cytokine microenvironment on T cell/B cell cross‐talk. Results: A proinflammatory cytokine profile defined by high levels of CXCL10, interleukin‐6 (IL‐6), IL‐2, and tumor necrosis factor characterized a distinct group of patients in the 4 systemic autoimmune diseases. In each disease, this proinflammatory cluster was associated with a specific circulating immune cell signature, more severe disease, and higher levels of autoantibodies, suggesting an uncontrolled proinflammatory Th1 immune response. We observed in vitro that B cells reinforce Th1 differentiation and naive T cell proliferation, leading to the induction of type 1 effector B cells and IgG production. This process was associated with an increase in CXCL10, IL‐6, IL‐2, and interferon‐γ production. Conclusion: This composite analysis brings new insights into human B cell functional heterogeneity based on T cell/B cell cross‐talk, and proposes a better stratification of patients with systemic autoimmune diseases, suggesting that combined biomarkers would be of great value for the design of personalized treatments.